Why should investors stay positive on the Asian real estate markets? - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
Asia’s real estate market has weakened in tandem with lower equity prices. Singapore is no exception. Gone (for now) is the frenzied buying that marked 2007 and 2008, as everyone hunkers down for a possible protracted slump in the global economy. Many property buyers are caught with assets declining in value. Should investors thus stay away from Asia’s property market? What are the challenges facing the industry players, and is there a recovery on the horizon?